User Multi Group Key Distribution Using Secret Sharing with Circulate Matrices Based on Diophantine Equation and Ecdh Key Exchange Protocol - Alghareeb, Eman Talib; Osipyan, Valeriy (Informatica, 2023)
The majority of currently used conventional group key distribution protocols are primarily created for a single group. But group communications are becoming more and more popular as networks improve quickly. So all participating users must share or exchange a secure group key beforehand in order to protect communication and multi-group key installations are necessary for many group-oriented applications at the moment. This allows users to join numerous groups at once. A novel type of user-oriented multi-group key setups employing secret sharing was recently provided by C.F. Hsu et al. in 2018 (UMKESS). This protocol, like many other group key establishment systems, is polynomial-based, requiring both the key generation center (KGC) and each group member to resolve t-degree approximating polynomials in order to distribute and retrieve the secret group key. N. Shruti et al in 2018 suggested a user-friendly group key distribution mechanism uses secret sharing with circulate matrices.in this article we have improved performance security of previous protocol by using two techniques, ECDH exchange protocol to generate sharing secret key with using it as key in term of Diophantine equations in second degree. Security analysis is displayed that our suggested technique more effective, secure, robust and achieves the key security, provides forward and back-ward secrecy, prevents insider and out sider attacks. Povzetek: izboljšanje varnosti delovanja protokola UMKGMTP.